Stock Selection Analysis on the IDX30 Stock Index Listed on the Indonesia Stock Exchange Using the Single Index Model - Ignatius Reysa Nugroho; William Tjong (Enrichment : Journal of Management, 2021)
This research is entitled Analysis of Share Selection on The Idx30 Stock Index Listed on The Indonesia Stock Exchange Using Single Index Model. This study aims to determine the optimal stock as a basis for decisions in determining investment in company shares that are in the IDX30 stock index listed on the Indonesia Stock Exchange (IDX) using the Single Index Model method. The research period used is January 2015 – December 2019. The population of this study is 30 stocks listed in the IDX30 stock index. The sample of this study was determined by purposive sampling with the criteria of stocks listed on the IDX30 index consecutively during the study period. So there are 19 stocks that became the sample of this study. The results of the analysis using the Single Index Model method, can form the best stock selection consisting of BBCA 56.94%, CPIN 9.34%, ICBP 17.91%, BBRI 9.29%, ADRO 3.39%, and TLKM 3.12%. The results of this study indicate that it is possible to build stock selections with maximum returns for a certain level of risk on the IDX30 stock index using the Single Index Model for the period January 2015 – December 2019.